OBEDIENCE LEVEL OF PREGNANT WOMEN IN CONSUMING IRON TABLETS IN THE WORKING AREA OF PUSKESMAS I DENPASAR SELATAN - Ni Komang Ayu Kosali Dewi; I Made Rodja Suantara; I Ketut Kencana (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2021)
Pregnant women are one of the groups prone to nutrition, often experiencing iron deficiency anemia. The prevalence of anemia in 2018 has increased compared to 2017, which was 2.11% to 9.22%. The government has implemented an anemia prevention program for pregnant women by giving iron tablets (TTD). Pregnant women in the third trimester must consume as many as 90 tablets of TTD. TTD consumption for pregnant women is strongly influenced by their knowledge, the allocation of TTD distribution by puskesmas, and family / husband support. The purpose of this study was to assess knowledge, obtained TTD rations, family / husband support, and assess adherence to consuming TTD in the work area of Puskesmas I Denpasar Selatan. The type of research used was Observational with a Cross Sectional approach with 48 samples. The results of the study showed that more than half (64.58%) had good knowledge, all mothers received TTD but there were still obedient candidates taking TTD, namely 20.83% and obedient, namely 79.17%. Most (66.67%) families / husbands have supported mothers to consume TTD. The better the knowledge about TTD the more obedient the consumption. As well as the better support provided, the mother will be motivated to obey consuming TTD. It can be concluded that most (64.58%) have good knowledge, all pregnant women receive TTD, as much as 66.67% of families / husbands support to consume TTD, and more than half (79.17%) obey consuming TTD.